Effects of two Fluoride Mouthwashes on Surface Topography and Frictional Resistance of Orthodontic Wires - Eilnaz Ehrami; Alireza Omrani; Masood Feizbakhsh (Tehran University of Medical Sciences, 2022)
Objectives: We compared the effects of fluoride mouthwashes on surface topography of orthodontic wires, and static and kinetic frictional forces between stainless-steel (SS) orthodontic brackets and SS and nickel-titanium (NiTi) archwires. Materials and Methods: This in vitro, experimental study evaluated 240 standard SS maxillary central incisor brackets and 0.018-, and 0.025×0.019-inch NiTi and SS archwires. Different combinations of wire diameters and wire types were exposed to artificial saliva (control), 0.05% sodium-fluoride (NaF) for 1 minute daily, or 0.2% NaF for 1 minute weekly (37°C) for 3 months. The wires were pulled in the bracket slots by 5mm in a universal testing machine (10mm/minute). The static and kinetic forces were measured. The surface topography of the wires was inspected under a scanning electron microscope (SEM). Three-way ANOVA followed by Bonferroni post-hoc tests were used for statistical analysis (P<0.05). Results: The mean static and kinetic frictional forces of 0.025×0.019- inch NiTi wired in the 0.05%NaF group were significantly greater than the SS wire. The mean kinetic frictional force in the 0.05%NaF group was significantly greater than the 0.2%NaF and artificial saliva groups for all wires. The mean static and kinetic forces in 0.2%NaF were significantly greater than in artificial saliva. In all groups, larger wires showed higher mean frictional forces. SEM results revealed higher wire surface roughness in the 0.05%NaF group followed by the 0.2%NaF group. Conclusion: Weekly use of 0.2%NaF mouthwash is recommended during sliding mechanics to minimize frictional forces between SS and NiTi wires and SS brackets.